Does Diversification Strategy Play An Eminent Role In The Current Turbulence Of Digital Economy: A Strategic Approach - Oroh , Augustinus Nicolaas Hillebrandes (International Journal of Industrial Management, 2021)
Most industry players are dubious whether current digital technology is strongly affecting the long traditional demand and supply economy while scholars believe that companies need to have valuable and unique resources, excellent and agile capabilities, and the capacity of aligning their core competencies to lead the industry and therefore sustaining its competitive advantage. Companies are fighting with the aggressive movements by their competitors in the changing markets and facing very dynamic full of surprises environmental turbulence. We reveal the Environment Serving Organization concept helps companies to be well prepared in advance and applicable at all turbulence levels when the overall economy is at high uncertainty. By exploring diversification based on Ansoff Growth Matrix and using the regression and mediation models, this is one of the first papers that investigates the Environmental Turbulence level as a probable mediator in the intense relationship between diversification strategy and strong firm performance.